Circulating Immune Complexes after Renal Transplantation: CORRELATION OF INCREASED 125I-C1q BINDING ACTIVITY WITH ACUTE REJECTION CHARACTERIZED BY FIBRIN DEPOSITION IN THE KIDNEY - Ooi, Yuet M.; Ooi, Boon S.; Vallota, Enrique H.; First, Martin R.; Pollak, Victor E. (The Journal of Clinical Investigation, 1977)
To assess the role of circulating immune complexes in the pathogenesis of acute rejection, sera were measured for such complexes by the 125I-C1q binding assay in 45 normal subjects, 24 allografted patients undergoing acute rejection, and in 11 allografted patients in a quiescent phase. Increased C1q-binding activity (C1q-BA) was detected in 14 patients with acute rejection, 9 of whom had renal biopsies showing fibrin deposition in the vasculature together with cellular infiltrates in the tubulo-interstitial structures; renal histology was not available in the other 5 patients. The other 10 patients with acute rejection, whose biopsies showed only cellular infiltrates, and the 11 patients in a quiescent phase posttransplantation did not have increased levels of serum C1q-BA. Of the group with increased serum C1q-BA, serial studies in eight patients showed a correlation between increased serum C1q-BA and the occurrence of rejection; with reversal by therapy, serum C1q-BA returned to within normal levels. Complexes from six patients were analyzed by sucrose density gradient ultracentrifugation to have sedimentation coefficients ranging from 15S to 18.4S. After acid dissociation and analysis by double-diffusion techniques, C1q-reactive complexes were shown to contain IgG. Immunofluorescent studies done in five renal biopsies from this group revealed granular deposits of immunoglobulin, and (or) less frequently, of complement in the glomeruli or the tubular basement membranes. The findings suggest that circulating immune complexes may mediate the type of acute rejection characterized by fibrin deposition in the kidney. The role of circulating immune complexes arising from the recipient's original kidney disease could be excluded in 10 patients with humoral rejection, inasmuch as the underlying renal pathology was of a “nonimmunologic” nature; this was corroborated by sequential studies in six patients in whom circulating immune complexes could not be demonstrated before rejection. The participation of administered antilymphocyte globulin (ALG) as an antigen also appears to be excluded in four patients, two who were not given ALG, and in two of whom episodes of rejection occurred unrelated temporally to ALG administration.